2004
DOI: 10.1002/macp.200400120
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous‐Crystalline PSnPEOn Heteroarm Star Copolymers: Crystallinity and Crystallization Kinetics

Abstract: Summary: The crystallization behavior and kinetics of poly(ethylene oxide) in polystyrene/poly(ethylene oxide) heteroarm star copolymers were studied by differential scanning calorimetry and optical microscopy. A comparison between star and linear amorphous‐crystalline block copolymers showed that the macromolecular architecture is an important factor affecting crystallinity. The following points were observed: the equilibrium melting point is higher in the star copolymers, the crystallinity reduces as the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…To achieve HEX cylindrical morphology with P3DDT (or P3HT) matrix, one can use different macromolecular architecture from linear block copolymer, because the molecular architecture of a block copolymer is one of the important parameters to tune morphology and thermal properties. Among various macromolecular architectures, miktoarm star copolymer is a star polymer that consists of heteroarms with different chemical composition or molecular weight, and has attracted great interest for its distinct behavior compared with corresponding linear block copolymers. Goseki et al synthesized A 2 B miktoarm star copolymer composed of two polystyrene (PS) arms and one polyhedral oligomeric silsesquioxane-containing poly­(methacrylate) (PMAPOSS). Cylindrical microdomains of the PMAPOSS were obtained due to curvature effect at the interface, while these microdomains were not observed in linear PS- b -PMAPOSS diblock copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve HEX cylindrical morphology with P3DDT (or P3HT) matrix, one can use different macromolecular architecture from linear block copolymer, because the molecular architecture of a block copolymer is one of the important parameters to tune morphology and thermal properties. Among various macromolecular architectures, miktoarm star copolymer is a star polymer that consists of heteroarms with different chemical composition or molecular weight, and has attracted great interest for its distinct behavior compared with corresponding linear block copolymers. Goseki et al synthesized A 2 B miktoarm star copolymer composed of two polystyrene (PS) arms and one polyhedral oligomeric silsesquioxane-containing poly­(methacrylate) (PMAPOSS). Cylindrical microdomains of the PMAPOSS were obtained due to curvature effect at the interface, while these microdomains were not observed in linear PS- b -PMAPOSS diblock copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…As known, for linear and crystalline polymers, it is possible that the LB deposition might lead to some changes of the orientation 38 and crystallinity 39 of the chains but does not affect much less ordered polymers such as star polymers. 40 Moreover, previous studies in our group have utilized X-ray reflectivity to study Langmuir monolayers of branched polymers at the air/water interface in comparison to the LB monolayer. 41,42 The results showed that the organization or assembly of the star polymers is not affected by the transfer process with the star polymers becoming somewhat squashed after transferring to the air/solid interface as suggested in this study as well (Figure 5).…”
Section: ■ Introductionmentioning
confidence: 99%